Peran Return On Asset (ROA) Sebagai Variabel Intervening Pada Ukuran Perusahaan Dan Leverage Terhadap Harga Saham Perbankan Syariah Indonesia - Ningrum, Galuh Kharisma; Sriyono, Sriyono; Setiyono, Wisnu Panggah (Universitas Islam Kadiri, 2025)
Islamic banking is a financial institution that functions as an intermediary for parties who have excess funds with parties who lack funds to carry out business activities and other activities in accordance with Islamic law. The development of Islamic banking in Indonesia in recent years has shown significant growth, ho wever, it has not been followed by an increase in stock prices. This will cause investors to be uninterested in buying shares in Islamic Banks. This study aims to determine the effect of company size and leverage on stock prices through return on assets (ROA) as an intervening variable in Indonesian Islamic banking. The results of this study show that firm size and leverage have a significant positive effect on stock price, while unexpectedly, ROA has a significant negative effect on stock price. On the other hand, ROW was shown to significantly mediate the effect of firm size on stock price, but not the effect of leverage. The effect of leverage on stock price is driven more by market perceptions of risk and growth potential, rather than how efficiently the company manages its assets through debt financing. This means that investors assess the use of debt more as a company's external strategy that does not always reflect an increase in internal profitability performance.